Study of impurity effects on CFETR steady-state scenario by self-consistent integrated modeling. (5th October 2017) - Shi, Nan; Chan, Vincent S.; Jian, Xiang; Li, Guoqiang; Chen, Jiale; Gao, Xiang; Shi, Shengyu; Kong, Defeng; Liu, Xiaoju; Mao, Shifeng; Xu, Guoliang
Abstract: Impurity effects on fusion performance of China fusion engineering test reactor (CFETR) due to extrinsic seeding are investigated. An integrated 1.5D modeling workflow evolves plasma equilibrium and all transport channels to steady state. The one modeling framework for integrated tasks framework is used to couple the transport solver, MHD equilibrium solver, and source and sink calculations. A self-consistent impurity profile constructed using a steady-state background plasma, which satisfies quasi-neutrality and true steady state, is presented for the first time. Studies are performed based on an optimized fully non-inductive scenario with varying concentrations of Argon (Ar) seeding. It is found that fusion performance improves before dropping off with increasing Z eff, while the confinement remains at high level. Further analysis of transport for these plasmas shows that low- k ion temperature gradient modes dominate the turbulence. The decrease in linear growth rate and resultant fluxes of all channels with increasing Z eff can be traced to impurity profile change by transport. The improvement in confinement levels off at higher Z eff . Over the regime of study there is a competition between the suppressed transport and increasing radiation that leads to a peak in the fusion performance at Z eff ( 2.78 for CFETR). Extrinsic impurity seeding to control divertor heat load will need to be optimized around this value for best fusion performance.